Chalcogenide Materials for Energy Conversion Pathways to Oxygen and Hydrogen Reactions - Alonso-Vante, Nicolas (Nanostructure Science and Technology,, 2018)
This book addresses electrocatalysis based on chalcogenides, particularly in the nanoscale domain. Special attention is paid to the hydrogen evolution reaction (HER) and the oxygen reduction reaction (ORR). The book provides an introduction to materials synthesis; the basic principles of electrocatalysis; related precious metal versus non-precious metal catalytic center chalcogenides as well as supports; and the role of such supports in stabilizing the catalytic centers. In short: pursuing a bottom-up approach, it covers the properties of this class of electrocatalysts and examines their applications in low-temperature fuel systems such as microfluidic fuel cells for portable devices. Accordingly, it is ideally suited for all professionals and researchers interested in electrochemistry, renewable energy and electrocatalysis, and non-precious metal centers for chemical energy conversion.